2004
DOI: 10.1073/pnas.0402088101
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia induces adhesion molecules on cancer cells: A missing link between Warburg effect and induction of selectin-ligand carbohydrates

Abstract: Cancer cells undergo distinct metabolic changes to cope with their hypoxic environment. These changes are achieved at least partly by the action of transcriptional factors called hypoxia-inducible factors (HIFs). We investigated gene expression in cultured human colon cancer cells induced by hypoxic conditions with special reference to cell-adhesion molecules and carbohydrate determinants having cell-adhesive activity by using DNA-microarray and RT-PCR techniques. Hypoxic culture of colon cancer cells induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
148
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(162 citation statements)
references
References 45 publications
14
148
0
Order By: Relevance
“…A similar phenomenon was found by labelling with HPA and anti-sLe a and no difference in the binding pattern or intensity was detected between both strains of mice. This observation leads to the idea that the expression of selectin ligands of the tumour cells can vary and that their selectin-binding pattern is probably influenced by the different environment of the tumour cells, as already shown by Koike et al (2004), who showed that oxygenation influences selectin-binding site expression. This difference in expression pattern is explained by the observation that transformational effects, such as growth to high cell densities, 2D vs 3D growth or hypoxia, lead to an alteration of carbohydrate patterns between tumour cells grown in vivo and in vitro (Warren et al, 1978).…”
Section: Discussionmentioning
confidence: 93%
“…A similar phenomenon was found by labelling with HPA and anti-sLe a and no difference in the binding pattern or intensity was detected between both strains of mice. This observation leads to the idea that the expression of selectin ligands of the tumour cells can vary and that their selectin-binding pattern is probably influenced by the different environment of the tumour cells, as already shown by Koike et al (2004), who showed that oxygenation influences selectin-binding site expression. This difference in expression pattern is explained by the observation that transformational effects, such as growth to high cell densities, 2D vs 3D growth or hypoxia, lead to an alteration of carbohydrate patterns between tumour cells grown in vivo and in vitro (Warren et al, 1978).…”
Section: Discussionmentioning
confidence: 93%
“…The increment in the expression of these genes occurs in the advanced stage of cancers and partially explains the enhancement of sialyl Lewis a/x in advanced cancers. 39) The enhanced expression of sialyl Lewis a/x , however, is already obvious in the early stages of cancers.…”
Section: Induction Of Sialyl Lewis A/x Expression In Epithelial Cancementioning
confidence: 99%
“…[6][7][8][9] To assess vascularization, frozen sections of the tumors were stained for the mouse CD31, an endothelial cell determinant and examined by fluorescence microscopy. As shown in Figure 5a, there is a striking difference between the tumors with respect to the vascular architecture and microvessel density.…”
Section: Vasculogenesis Is Inhibited In Fut1-derived Tumorsmentioning
confidence: 99%
“…3 Besides, several lines of evidence from selectin-deficient mice studies pointed out the contribution of selectins in facilitating tumor growth and progression. 4,5 In particular, E-selectin and its sLex-containing glycoconjugate ligands have been shown to be involved in the essential events of tumor angiogenesis, [6][7][8][9] including the fact that coinjection of tumor cells expressing high level of sLe x together with endothelial cells constitutively expressing E-selectin, has been found to promote tumor angiogenesis and growth. 10 We have recently succeeded in strongly blocking the expression of sLex on digestive cancer cells by a virally-delivered a(1,2)-fucosyltransferase-I (FUT1).…”
mentioning
confidence: 99%